Versuch eines sozialökonomischen Klassifikationsmodells kleinbäuerlicher Familien in Mexiko.: Dargestellt am Beispiel zweier Ejido-Gemeinden im zentralen Hochland (Projektsgebiet der DFG von Puebla-Tlaxcala) - Sander, Hans-Jörg (ERDKUNDE, 1973)
The paper is divided into two parts. In the first, the results of two socio-geographical village studies within the area of the Deutsche Forschungsgemeinschaft's Central Mexican Highlands project (Puebla-Tlaxcala region) are pre sented. The second part is devoted to an attempt, based on the experience of the village studies, to develop a model of the socio-economic differentiation of peasant families in Mexico. The basic consideration of the model is the empirically-grounded assumption that the socio-economic differentiation process proceeds from an undifferentiated isolated subsistence-economy society to a differentiated, integrated urban (industrial) society. As a description of this process the model offers five socio-economic transition stages, each characterised by an increasing degree of agricultural specialisation and the drift to occupations outside agriculture.